Green Human Resources Practices and Person-Organization Fit: The Moderating Role of the Personal Environmental Commitment - Francisco Cesário; Ana Sabino; Ana Moreira; Teresa Azevedo (Emerging Science Journal, 2022)
Based on the 2030 Agenda of the United Nations (UN), where 17 Sustainable Development Goals (SDGs) are identified, the present study aims to (1) propose a measure for the perception of green human resources management practices; (2) investigate its relationship with the employees’ person-organization fit, and (3) analyze the moderating role of personal environmental commitment in the relationship between the perception of green human resources management practices and employees’ person-organization fit. A quantitative and hypothetical-deductive approach was used, and a sample of 204 Portuguese employees responded to an online questionnaire. The results showed (1) that the proposed measure for the perception of green HR practices was adapted to the Portuguese population and showed excellent internal consistency; (2) a significant and positive relationship between perceived green HR practices and person-organization fit; and (3) that this relationship can be moderated by high personal environmental commitment. The study presents novelty and contributes to the existing literature concerning green HR practices by proposing an adapted measure, relating it to person-organization fit, and verifying the moderated role of personal environmental commitment. Thus, the effective implementation of green HRM practices is highlighted to promote positive consequences in the organization and the employees. Doi: 10.28991/ESJ-2022-06-05-02 Full Text: PDF